Rational Principles of Pianoforte Technique - Cortot, Alfred 1877-1962; Roy-Metaxas, R. Le (Paris Salabert)
This book provides a comprehensive method divided into five chapters covering aspects such as, evenness, independence and mobility of the fingers, passing under of the thumb - scales and arpeggios, the technique of double notes and polyphonic playing, the technique of extensions, the technique of the wrist and the execution of chords.
Keywords: Method